Optimalisasi Pemanfaatan Mikroorganisme Lokal (MOL) untuk Meningkatkan Kesuburan Tanah pada Sistem Pertanian - Arini (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the effectiveness of Local Microorganisms (MOL) in improving soil fertility within sustainable agricultural systems. A field experimental method was applied using four MOL concentration treatments: 0%, 20%, 40%, and 60%. Observed parameters included physical, chemical, and biological soil properties, as well as plant growth responses. The results indicated that MOL application significantly increased nitrogen, phosphorus, and potassium content, improved soil porosity, and enhanced microbial populations. MOL treatments at concentrations of 40–60% provided the most optimal improvements in soil fertility and plant growth. Overall, MOL proved to be an effective, low-cost, and environmentally friendly technology that supports the implementation of sustainable agriculture.